A Monte Carlo Simulation to Estimate the Additional Cost Associated With Adverse Medication Events Leading to Intraoperative Hypotension and/or Hypertension in the United States. Issue 8 (4th December 2021) - Nanji, Karen C.; Shaikh, Sofia D.; Jaffari, Alireza; Franz, Calvin; Bates, David W.
Abstract : Objectives: Intraoperative hypertension and hypotension are common and often related to adverse medication events (AMEs). The study objective is to estimate the annual additional fully allocated costs to the U.S. healthcare system related to AMEs associated with clinically significant intraoperative hypertension and hypotension. Methods: Using anesthesia-trained observers in randomly selected operating rooms, we estimated the rates of clinically significant intraoperative hypotension and hypertension. We conducted systematic literature reviews to estimate incidence and additional costs of acute kidney injury (AKI), acute myocardial injury, and stroke after intraoperative hypotension and hypertension. We used Monte Carlo simulation to estimate annual costs to the U.S. healthcare system. Results: Intraoperative hypotension (mean arterial pressure <55 mm Hg for >6 minutes) occurred in 11 of 277 operations (3.97%), hypotension (>30% drop from baseline mean arterial pressure in patients with coronary artery disease) in 9 operations (3.25%) and hypertension in 14 operations (5.05%). After hypotension, incremental incidence of AKI was 1.46% (additional cost $17, 289/case), acute myocardial injury was 0.75% ($21, 340/case), and stroke was 0.05% ($19, 903/case). After hypertension, incremental stroke incidence was 4.76% ($28, 320/case). Annually in the United States, we estimated 11, 513 cases of AKI, 5914 of acute myocardial injury, 345 of stroke after intraoperative hypotension, and 47, 774 cases of stroke after intraoperative hypertension, costing the U.S. $1.7 billion (90% confidence interval, $1.4–$2.0 billion), of which $923 million (90% confidence interval, $763–$1101 million) is preventable. Conclusions: Adverse medication events related to blood pressure are frequent, costly, and can cause considerable patient harm. Cost estimates for these events may provide a means of prioritizing safety improvements to reduce cost of care and improve patient outcomes.